Book Review: Transitions and Tools that Support Scholars’ Success by Mary Renck Jalongo and Olivia N. Saracho - Dharmarathna, D.G. (Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, 2020)
The prime duty of an academic is to contribute to the economy of knowledge. Academics find new knowledge through research and they disseminate it through lectures and scholarly works. Researchers face a real challenge when they want to publish their work. A scholars’ success solely depends on impactful publications. In accordance with this argument, the book titled ‘Writing for Publication’ discusses the transitions and tools that support a scholars’ success.